Comparação entre dois métodos de detecção de DNA de papilomavírus humano em carcinoma epidermoide de lábio - Demathe, Adriana (2010)
Introduction: Human papillomavirus (HPV) has been currently associated with oral carcinogesis. The methodology applied in virus detection is one of the main reasons for the great variability observed in HPV detection. Objectives: This study compared HPV DNA detection efficiency in lip squamous cell carcinoma samples (SCC) using viral DNA amplification by PCR or nPCR. Methods: Thirty three samples of lip squamous cell carcinoma were selected. DNA extractions were performed with QIAamp DNA minikit. The internal control was b-globin gene. Thirty out of 33 initial samples were positive for b-globin gene, which were employed to detect viral DNA. The amplification of viral DNA was compared by PCR method through MY09/MY11 oligonucleotides and nPCR through MY09/MY11 oligonucleotides in the first stage and GP5+/GP6+ in the second stage. HeLa cells were used as positive control for HPV DNA presence and the amplification mixture without DNA as negative control. The analysis of PCR and nPCR products for HPV DNA was performed through gel electrophoresis in polyacrylamide at 8%. Results: HPV DNA amplification was verified in two cases by the use of PCR method. HPV DNA presence was verified in 13 out of 30 samples by the use of nPCR. Conclusion: HPV DNA detection of lip SCC increased sixfold in the studied cases with the employment of nPCR.